The Cotton GhWRKY91 Transcription Factor Mediates Leaf Senescence and Responses to Drought Stress in Transgenic Arabidopsis thaliana - Gu, Lijiao; Ma, Qiang; Zhang, Chi; Wang, Congcong; Wei, Hengling; Wang, Hantao; Yu, Shuxun (Frontiers in Plant Science, 2019)
WRKY transcription factors (TFs) play essential roles in the plant response to leaf senescence and abiotic stress. However, the WRKY TFs involved in leaf senescence and stress tolerance in cotton (Gossypium hirsutum L.) are still largely unknown. In this study, a WRKY gene, GhWRKY91, was isolated and thoroughly characterized. Transcriptional activity assays showed that GhWRKY91 could activate transcription in yeast. The expression pattern of GhWRKY91 during leaf senescence and in response to abscisic acid (ABA) and drought stress was evaluated. β-Glucuronidase (GUS) activity driven by the GhWRKY91 promoter in transgenic Arabidopsis was reduced upon exposure to ABA and drought treatments. Constitutive expression of GhWRKY91 in Arabidopsis delayed natural leaf senescence. GhWRKY91 transgenic plants exhibited increased drought tolerance and presented delayed drought-induced leaf senescence, as accompanied by reinforced expression of stress-related genes and attenuated expression of senescence-associated genes (SAGs). Yeast one-hybrid (Y1H) assays and electrophoretic mobility shift assays (EMSAs) revealed that GhWRKY91 directly targets GhWRKY17, a gene associated with ABA signals and reactive oxygen species (ROS) production. A transient dual-luciferase reporter assay demonstrated that GhWRKY91 activated the expression of GhWRKY17. Our results suggest that GhWRKY91 might negatively regulate natural and stress-induced leaf senescence and provide a foundation for further functional studies on leaf senescence and the stress response in cotton.